Understanding the Gains and Challenges of Democratization Process in Sub-Saharan Africa: Is Democratic Progress Under Threat? - Pelin Aliyev (İnsan & Toplum)
The aim of this research is to examine the achievements and challenges of the democratization process in Sub-Saharan Africa and to answer whether democratic progress is under threat. Focusing on Burkina Faso, Mali, and Niger—countries with regional and historical similarities—the research seeks to understand the common dynamics of democratic development in these countries. The research employs a comparative framework to analyze their democratization processes. The findings of the research highlight two main conclusions: First, all the three countries have experienced a significant increase in voter participation, stronger public support for democracy and electoral processes and a notable opposition to one-man and one-party rule. Second, the democratization processes are frequently interrupted by military coups, authoritarian tendencies of leaders and electoral violence. While the research acknowledges the substantial progress made, it also emphasizes that significant challenges persist, which continues to weaken political institutions and processes. These challenges continue to hinder the full realization of democratic governance in these three countries and lead to regime changes.